Enforcement of Immigration Law Against Human Smuggling Especually Illegal Foreign Labor in Indonesia : Normative – Empiric Axiology - Fajar Dimas N. I; M Irfan Singke (Polteknik Imigrasi, 2021)
Transnational crime has the potential to occur in Indonesia, which is a developing country. Transnational crime is not only driven by the free trade factor and weak law enforcement in Indonesia, but also by the geographical area of ​​Indonesia itself. In the midst of many national problems that are currently happening and require serious attention, one of the serious concerns is people smuggling or people smuggling. Law enforcement against immigration crimes, especially the problem of misuse of foreign workers' residence permits by law enforcement officers, especially PPNS investigators is still very weak. This can be seen in the development of the issue of illegal foreign workers which is being discussed in the community. This situation needs serious attention from the government, especially law enforcement. Enforcement of illegal foreign workers can be carried out administrative actions in the form of paying fees/fines, deportation, revocation of business licenses, and if the conditions for employing foreign workers are not met, the licensing agency can repatriate foreign workers to their countries of origin, and deterrence or criminal sanctions with the threat of imprisonment. The policy of determining in the future should stipulate a special minimum and a special maximum in criminal sanctions, in addition to mapping the division of roles so that there is no generalization of the imposition of criminal sanctions accompanied by the determination of criminal rules that are oriented towards smugglers and the people being smuggled.